Bioinformatics-Driven Optimization of Wheat Breeding by Integrating Genomic Data Analysis with Phenotypic Traits - Hussein Ramy Riad; Alkhafaij Mahdi Abdulkhudur; Madhavi Karanam (SHS Web of Conferences)
The integration of sophisticated bioinformatics tools and techniques in the field of wheat breeding is a revelatory one that has transformed the field with an all-around way of developing improved wheat varieties. To identify and localize genes related to yield, disease resistance, and drought tolerance, QTL mapping is used. Therefore, MAS can be utilized by breeders to utilize these identified genetic markers to more quickly identify individuals that perform well under certain conditions for selection and to improve the efficiency and accuracy of breeding decisions. High-density genetic maps by using Next Generation Sequencing (NGS) and Genotyping by Sequencing (GBS) can further provide a view of the genome and therefore more precise QTL mapping. By applying Principal Component Analysis (PCA) to reduce the dimensionality of highly complex datasets and utilize Linear Mixed Models (LMM) to solve the complex traits problem with the consideration of the fixed and random effects, respectively, we have successfully improved trait prediction and QTL identification. Integration of such advanced techniques into wheat breeding programs allows future crops to be developed with increased yield, resistance to disease, and better adaptability to different environmental conditions. The purpose of this paper is to take the current synergistic benefits of genomic and phenotypic data for breeding methodologies and incorporate this into supporting global food security and sustainably growing agriculture. The research aims to demonstrate the potential of these bioinformatics-driven techniques to further our knowledge of wheat genetics and to improve the approaches used in breeding to solve the problems of modern agriculture. The study's results showed that these most powerful QTLs for yield and disease resistance had LOD scores up to 4.9 (strong genetic associations). Genomic Estimated Breeding Values (GEBV) showed that plant ID 4 had the highest value of 6.7, and is a top Plant ID for breeding programs. In addition, the result of the Phenotypic Plasticity Index (PPI) analysis indicated Plant ID 5 being the most adaptive with an adaptability score of 0.85, denoting its ability to withstand environmental variability more effectively compared with the other Plants. The integration of advanced bioinformatics methods in reverse bioselction and breeding precision and efficiency has made unprecedented advances as indicated by this numerical insight.